2010
DOI: 10.1111/j.1365-294x.2010.04708.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of shattering loci in U.S. weedy rice

Abstract: Cultivated rice fields worldwide are plagued with weedy rice, a conspecific weed of cultivated rice (Oryza sativa L.). The persistence of weedy rice has been attributed, in part, to its ability to shatter (disperse) seed prior to crop harvesting. In the United States, separately evolved weedy rice groups have been shown to share genomic identity with exotic domesticated cultivars. Here, we investigate the shattering phenotype in a collection of U.S. weedy rice accessions, as well as wild and cultivated relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
175
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(203 citation statements)
references
References 53 publications
26
175
0
2
Order By: Relevance
“…According to De-Wet and Harlan (1975), weedy rice originated from the selection and adaptation of wild rice to agricultural habitats. In regions where no wild rice has been grown, weedy rice may instead originate from cultivated rice through de-domestication with adaptive mutations and the accumulation of beneficial mutants (Ishikawa et al 2005;Cao et al 2006;Reagon et al 2011;Thurber et al 2010;He et al 2014;Qiu et al 2014;Lu et al 2016;Li et al 2017;Qiu et al 2017). In the case of Brazil and Italy, where no wild Oryza types are indigenous, contamination of seed stocks with wild Oryza species has been proposed as a source of weedy rice (Carney 2004;Grimm 2014).…”
Section: Origin and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to De-Wet and Harlan (1975), weedy rice originated from the selection and adaptation of wild rice to agricultural habitats. In regions where no wild rice has been grown, weedy rice may instead originate from cultivated rice through de-domestication with adaptive mutations and the accumulation of beneficial mutants (Ishikawa et al 2005;Cao et al 2006;Reagon et al 2011;Thurber et al 2010;He et al 2014;Qiu et al 2014;Lu et al 2016;Li et al 2017;Qiu et al 2017). In the case of Brazil and Italy, where no wild Oryza types are indigenous, contamination of seed stocks with wild Oryza species has been proposed as a source of weedy rice (Carney 2004;Grimm 2014).…”
Section: Origin and Evolutionmentioning
confidence: 99%
“…Sequence comparisons of the mutation site of the gene revealed its presence in all the domesticated rice cultivars. Thurber et al (2010) evaluated allelic identity and the diversity of shattering locus sh4 in US weedy rice. The haplotypes contained a single derived mutation at the sh4 locus.…”
Section: Seed Shatteringmentioning
confidence: 99%
“…Additionally, QTL analysis identified sh4 between SSR markers RC4-123 and RM280, which had a physical distance of ~1360 kb in the O. sativa genome. Thurber et al (2010) assessed allelic identity and diversity at the major shattering locus, sh4, in weedy rice. They demonstrated that all cultivated and weedy rice, regardless of the population, shared similar haplotypes at sh4 and all contained a single mutation associated with decreased seed shattering.…”
Section: Discussionmentioning
confidence: 99%
“…). An even more striking mitigation gene to use would be the various antiseed shatter genes (Thurber et al, 2010;Akasaka et al, 2011;Zhu et al, 2012), which would prevent the weed from reseeding itself. A crop-related weed with an antiseed shatter gene growing in the crop will be harvested with the crop, and will not reseed itself, if the farmer uses weed-free certified seed in the next season.…”
Section: Four Examples Of Intractable Weeds Needing Potentially Diffementioning
confidence: 99%